HUBUNGAN MOTIVASI IBU DAN PERAN KADER DENGAN KEAKTIFAN DALAM MENGIKUTI KEGIATAN POSYANDU BALITA DI WILAYAH KERJA PUSKESMAS ENAM LINGKUNG KABUPATEN PADANG PARIAMAN - Renty Ahmalia; Rostri Zaelfi (Universitas Baiturrahim, 2019)
Coverage of visits to mothers of children under five in Indonesia in 2016 reached 80.01%, whereas in 2017 coverage of visits of mothers of toddlers to Posyandu declined to 79.34%. Provinces that were still relatively low in achievement were Gorontalo (57.6%), North Kalimantan (58.6%), South Kalimantan (59.4%), Papua (64.8%) and West Sumatra (76.8%). This research is a quantitative study with a cross sectional design or approach. The purpose of the study was to find out the relationship between maternal motivation and the role of cadres with activeness in participating in the activities of Posyandu toddlers in the work area of the Six Lingkung Health Center in Padang Pariaman District which was carried out in July 2019 with a sample of 62 respondents, a total sampling technique. The statistical test used is chi-square. The results of this study have a relationship between maternal motivation and activeness in participating in the Posyandu for toddlers in the area of the Six Lingkung Health Center in Padang Pariaman District (p value = 0.044). (p value = 0.023). It is hoped that the Puskesmas will remind cadres to increase their role, especially in disseminating information to mothers. Cadres need to create social networks or communication networks that can facilitate the delivery of information to mothers such as creating a special whattsapp group of mothers who have toddlers, so that with this group, cadres can easily convey information to all mothers who live in the Posyandu working area